2005
DOI: 10.1507/endocrj.52.183
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Hypothalamo-pituitary-adrenal Axis and Changes in the Size of Adrenal Glands in Acute Brucellosis

Abstract: Abstract. The aim of the study was to investigate the hypothalamo-pituitary-adrenal (HPA) axis by ACTH stimulation test and the changes in adrenal size in acute brucellosis before and after therapy in a prospective study. Sixteen patients with acute brucellosis and 15 healthy subjects were included in the study during the last two years. Cortisol levels were assessed before, 30 and 60 minutes after ACTH (250 mg i.v.) injection and the size of the adrenals was measured in both groups. Mean basal cortisol levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The cortisol/DHEA ratio is abnormal under various pathological conditions such as AIDS, rheumatoid arthritis, and tuberculosis (18)(19)(20). In previous studies, significantly higher levels of cortisol in serum were reported in patients with acute brucellosis than in brucellosis patients at the end of antibiotic treatment or than in healthy subjects (21). In addition, adrenal glands are enlarged in patients with acute brucellosis but return to normal size after therapy (21).…”
Section: Tion Most Of Them Secreted By Macrophages (Such As Interleumentioning
confidence: 97%
“…The cortisol/DHEA ratio is abnormal under various pathological conditions such as AIDS, rheumatoid arthritis, and tuberculosis (18)(19)(20). In previous studies, significantly higher levels of cortisol in serum were reported in patients with acute brucellosis than in brucellosis patients at the end of antibiotic treatment or than in healthy subjects (21). In addition, adrenal glands are enlarged in patients with acute brucellosis but return to normal size after therapy (21).…”
Section: Tion Most Of Them Secreted By Macrophages (Such As Interleumentioning
confidence: 97%
“…However, there was no statistical difference between the cortisol levels in the acute and chronic phases. This may be explained by the fact that inflammation in the acute phase of tularemia was not as severe as other infections, such as acute brucellosis (4,10,13). One of the limitations of our study was that we could not include patients with severe forms of tularemia, such as pulmonary and typhoid forms, which have more potential to activate the HPA axis.…”
Section: Discussionmentioning
confidence: 95%
“…However, minimal or no adrenal response was detected in tularemia patients with moderate symptoms (8). Another experimental human study showed a decrease in free T 4 and an increase in 17-ketosteroid levels (12). This study is a clinical observation of adrenal response in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations